Analisa Tebal Perkerasan dengan Menggunakan Material Kinang Jingkion - Idie, Johanis Hs Ervans (Syntax Corporation, 2023)
The purpose of this study is 1) Analyzing the Pavement Layer Thickness using Kinang Jingkion material. 2) Calculating the Compaction Layer for CBR by pressing the Kinang Jingkion material. The local Kinang Jingkion material used in this study as a surface layer was taken from a location in the Yalimo Regency of Papua Province. As for Kinang Jingkion material, it is located in Habie River, Yahukimo Regency with a geographical point of 03o45'56.63